Implementasi Zakat Sebagai Pengurang Penghasilan Kena Pajak - Ai Nur Bayinah (Jurnal Akuntansi dan Keuangan Islam, 2015)
Zakat and tax synergies is a great need for a nation to support the growth of developmentand poverty alleviation. Some countries have done so by making a tax credit. Although indifferent way, the implementation of zakat as a deduction from taxable income is astrategic first step to be applied in Indonesia. Unfortunately, this regulation has not beenwidely known by the public, so not many are taking the benefits. However, this paperattempt to socialize its regulation, so people can understand how to implement and getthe benefit from it.